Presenilin Attenuates Receptor-Mediated Signaling and Synaptic Function - Parent, Angèle T. (J Neurosci, 2005)
Presenilin (PS) plays an essential role in intramembranous γ-secretase processing of amyloid precursor protein (APP) and several membrane-bound proteins. Here we report that selective accumulation of a membrane-tethered deleted in colorectal cancer (DCC) derivative (DCC-α) correlates with extensive neurite outgrowth in transfected neuroblastoma cells and axodendritic connectivity associated with increased spine density in cortical neurons derived from PS1(-/-) embryos, as well as wild-type neurons treated with γ-secretase inhibitors. cAMP-dependent signaling was also increased in both the neuroblastoma and cortical neuron systems. As a physiological consequence of increases in axodendritic connectivity and in the magnitude of cAMP-dependent signaling, short- and long-term glutamatergic synaptic transmission was enhanced in PS-deficient neurons. Together, these results demonstrate for the first time that PS-mediated γ-secretase activity attenuates receptor-mediated intracellular signaling pathways that are critical in regulating glutamatergic synaptic transmission and memory processes.